Key factors influencing clinical and functional outcomes in extracapsular proximal femur fractures: the role of early weightbearing - one-year follow-up cohort of 495 patients - Enrique Sanchez-Munoz; Beatriz Lozano-Hernanz; Daniel Vicente Velarde-Garrido; Leticia Alarma-Barcia; Victor Trivino Sanchez-Mayoral; Paula Romera-Olivera; Cristina Lopez Palacios (Medicinski glasnik, 2020)
Aim: To establish a correlation between immediate post-surgical weight bearing in extracapsular hip fractures and final functional outcome as well as to study the correlation between immediate post-surgical weight bearing and morbidity and mortality during the first year. Methods: Retrospective observational cohort study including 495 consecutive patients ?75 years old operated of extracapsular proximal femur fracture. Medical records were reviewed and information of demographic data, radiological evolution, time to weight-bearing, mortality rate, medical and surgical complications and final ambulation status were recorded. Results: Patients’ mean age was 87 years; 378 (76.4%) were females. One-year mortality rate was 21.2%. Immediate weight bearing was associated with: decreased hospital stays (7.5 days vs. 9.2 days; p=0.001) and decreased medical complications (78.3% vs. 82.3 %; p=0.02). Surgical complications prevalence was comparable (4.4% vs. 7.8 %; p=0.43) within the groups. Despite mortality rate was lower in patients with immediate weight bearing (21%) compared with delayed weight bearing (21.4%), the difference was not statistically significant (p=0.9). Conclusion: Immediate weight bearing was associated with shorter hospital stay and fewer medical complications, improving functional outcome. Also, no correlation was found between immediate weight bearing and increased surgical complications or mortality rate during first year after surgery.
Keywords: hip injuries; osteoporotic fractures; recovery of function; weight-bearing